Les choix de tracé des grandes infrastructures de transport : quelle place pour la biodiversité ? - Jean-Christophe Vandevelde (Développement Durable et Territoires)
Choice of large transport infrastructure routes: What place for biodiversity? Large linear transport infrastructures produce significant effects on biodiversity. The choice of infrastructure routes is thus a crucial step for avoiding some of the more damaging effects. Different methodological tools have been developed recently by contractors to integrate biodiversity into the decision-making process. The development and use of these tools are analyzed here as a political activity through the options and representations of biodiversity that are privileged. The participation mechanisms established can serve to record the results produced by these tools, but also call these latter into question, allowing the unveiling of the power dimension contained and often hidden in technical tools.